Metagenome analysis reveals potential microbial functions in topsoil of wheat–maize rotation system with five-year application of fertilizers - Shen, Yujun; Zhao, Lixin; Meng, Haibo; Cheng, Hongsheng; Ding, Jingtao; Wang, Jiarui; Dong, Shanshan; Zhang, Xi; Song, Liqiu; Zheng, Shengwei (International Journal of Agricultural and Biological Engineering, 2019)
Fertilization mode affects soil quality and ecological health. The effects of four fertilization regimens on lignocellulose content, readily degradable carbohydrate decomposition, and potential microbial functions in the topsoil of a wheat–maize rotation system between 2012 and 2017 were investigated. The fertilization regimens of control (control NFNB), high chemical fertilizer (HCF), high biochar plus low chemical fertilizer (HBLCF), and biochar-based fertilizer (BBF) were compared on soil fundamental properties, microbial structure, and potential function in soil carbohydrate degradation based on metagenome analysis. The diversity of carbohydrate-active enzyme genes in the topsoil microbial consortia in the four trials was primarily distributed within the ten ecologically most dominant phyla. Application of BBF was associated with the lowest decline in total nitrogen and P2O5 (2012-2017: 6.5% and 28.1%, respectively) and the most effective carbohydrate decomposition (2015-2017: 67.0% for cellulose and 59.9% for readily degradable carbohydrate). Carbohydrate transport and metabolism accounted for 6.0% of reads assigned functional classification under the BBF regimen. These findings reveal the ecologically functional diversity of topsoil microorganisms and suggest BBF application as a promising strategy for sustainable agriculture and beneficial to soil health. Keywords: biochar-based fertilizer, carbohydrate decomposition, genetic function, microbial community, topsoil DOI: 10.25165/j.ijabe.20191206.4849 Citation: Shen Y J, Zhao L X, Meng H B, Cheng H S, Ding J T, Wang J R, et al. Metagenome analysis reveals potential microbial functions in topsoil of wheat–maize rotation system with five-year application of fertilizers. Int J Agric & Biol Eng, 2019; 12(6): 177–184.